OPTIMALISASI PERAN KEPALA SEKOLAH DALAM PENGELOLAAN SUMBER DAYA UNTUK MENINGKATKAN MUTU PENDIDIKAN DASAR - Luthfi, Aulia; Mutiara, Alfina; Zakiyyah, Yumi; Muhibin, Ahmad; Sutopo, Anam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe in depth the principal's role in resource management and analyze the relationship between resource management and improving educational quality at SDN 3 Kudi. Optimizing resources, including human resources, school facilities, and budgets, is a key factor in supporting the achievement of educational goals. The principal plays a central role as a manager, leader, and prime mover in maximizing the potential of these resources. This research uses a qualitative descriptive approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that the principal plays a role in effectively managing resources, building collaboration between stakeholders, and creating a school climate conducive to learning. Optimal resource management has been shown to significantly improve educational quality, as reflected in student academic achievement, teacher professionalism, and the effectiveness of school programs. These findings underscore the importance of strengthening the principal's leadership capacity in addressing the challenges of educational quality in the modern era.